Evaluation of rainy-season forage crops in rotation with oat (Avena sativa) using alkali water irrigation - KUMAR, ASHOK; CHAWLA, K L (The Indian Journal of Agricultural Sciences, 2014)
A field study was conducted during 1996-98 at the Bhaini Majra farm, in Kaithal district of Haryana, to identify suitable rainy-season forage crop(s) for the areas where under-ground water is alkaline and is the only the source for irrigation. Three gypsum levels (0,'2 and 4 tonnes/ha) and 5 rainy-season crops, viz 'PC 6' sorghum [Sorghum bie%r (L.) Moench.], 'African Tall' maize (Zea mays L.), 'Giant Bajra' pearl millet [Pennisetum glaueum (L.) R.Br. emend. Stuntz.]; 'Hara Moti' sudan grass [Sorghum sudanense (Piper) Stapf.] and 'Improved' teosinte (Zea mexieana Schrad.), were tested in split-plot design under field conditions. Alkaline water (ECiw 1.8dS/m, residual sodium carbonate (RSC) 10.5 me/litre and sodium adsorption ratio (SAR) 8 was used for irrigatingthe crops. Sudan grass and sorghum were found to be more suitable for the situations where soils were moderatelyalkaline and irrigation water was also alkaline. These crops could be grown in rotation with oat (Avena sativa L.) crop in the winter season. , Application of gypsum at 2 tonnes/ha in the first year improved the yield of rainyseason forage crops by 15% oyer the control but during the third year there was 17.5% and 35% improvement in the yield owing to gypsum application at 2 and 4 tonnes/ha respectively.